Análise da aglomeração produtiva do setor de móveis de metal e sistemas de armazenagem e logística de Ponta Grossa - PR - Pagani, Regina Negri (2006)
The purpose of this study was to analyze the level of maturity and competitiveness of the sector of Steel Furniture and Storage and Logistics Systems in Ponta Grossa, PR, pondering on the perspectives of structuring a Local Productive Arrangement (LPA), according to the concepts and definitions presented by several authors in the literature. For this matter, a detailed and exhaustive study on productive agglomerations was done; it was studied the production organization of the sector, as well as its productive capacity and estimated profit; it was proposed a model to evaluate the competitiveness of agglomeration; the profile of the partner owners was traced, as well as the type of management adopted by the companies; it was evaluated the qualification of the workforce in the agglomeration; it was verified the level of interaction presently existent among the companies of the agglomerations and among the companies and local agents and, finally, the sector was characterized according to the typology of productive agglomerations presented in the literature. An exploratory research was accomplished through a case study in the sector, and from the 17 companies in the agglomeration, 15 were researched through a quantitative approach with qualitative complementary resources. The instruments used were questionnaires and interviews with partners and / or owners of each company. From the collected data the analysis was built, based on the objectives of the study. The analysis of the data collected in the field research, and confronted with the theoretical review, shows that the studied sector is an agglomeration of companies in its embrionary stage concerning the interaction among the companies, with great potential to become an LPA. The arguing for such statement is supported by the theories presented in this study.